Short Communication : Genetic analysis for identification of terminal heat tolerant genotypes in wheat - Mohanty, Soumitra; Mukherjee, Subhra; Dash, A. P.; Mandal, A. B. (The Indian Journal of Genetics and Plant Breeding, 2017)
A study was conducted to analyze divergence in 49 genotypes of bread wheat (Triticum aestivum L.) under terminal heat stress environment. The results indicated a good amount of genetic divergence among the wheat genotypes under heat stress. The genotypes were grouped into five clusters with maximum intra cluster distance of 70.392 (Cluster V) and maximum inter cluster distance was recorded between clusters III and V (72.11). Principal component analysis extracted seven principal components accounting 80.9% of total genetic variation. The identification of genotypes displaying heat stress tolerance may be useful in breeding.